ANALISIS UNSUR KOHESI DALAM WACANA BAHASA SMS (SHORT MESSAGE SERVICE) - Budi Hartanto (Indonesian Language Education and Literature, 2015)
This paper analyzes the response of short texts on the short message service (SMS), the devices used in analyzing the discourse of language short message service (SMS) is the cohesion that has a variation using marker cohesion, reference, substitution, ellipsis, conjunctions, and lexical cohesion (lexical cohesion). This paper uses data that all 15 samples senders respond to questions about the announcement at the reception CPNS Ngawi District. Languages write short message service (sms) a brief and 'mixed' is an interesting characteristic.